Activation of RAF/MEK/ERK and PI3K/AKT/mTOR pathways in pituitary adenomas and their effects on downstream effectors. - Dworakowska, D; Wlodek, E; Leontiou, C; Igreja, S; Cakir, M; Teng, M; Prodromou, N; Góth, M; Grozinsky-Glasberg, S; Gueorguiev, M; Kola, B; Korbonits, M; et al. (2009)
Raf/MEK/ERK and phosphatidylinositol 3-kinase (PI3K)/Akt/mammalian target of rapamycin (mTOR) cascades are key signalling pathways interacting with each other to regulate cell growth and tumourigenesis. We have previously shown B-Raf and Akt overexpression and/or overactivation in pituitary adenomas. The aim of this study is to assess the expression of their downstream components (MEK1/2, ERK1/2, mTOR, TSC2, p70S6K) and effectors (c-MYC and CYCLIN D1). We studied tissue from 16 non-functioning pituitary adenomas (NFPAs), six GH-omas, six prolactinomas and six ACTH-omas, all collected at transsphenoidal surgery; 16 normal autopsy pituitaries were used as controls. The expression of phospho and total protein was assessed with western immunoblotting, and the mRNA expression with quantitative RT-PCR. The expression of pSer217/221 MEK1/2 and pThr183 ERK1/2 (but not total MEK1/2 or ERK1/2) was significantly higher in all tumour subtypes in comparison to normal pituitaries. There was no difference in the expression of phosphorylated/total mTOR, TSC2 or p70S6K between pituitary adenomas and controls. Neither c-MYC phosphorylation at Ser 62 nor total c-MYC was changed in the tumours. However, c-MYC phosphorylation at Thr58/Ser62 (a response target for Akt) was decreased in all tumour types. CYCLIN D1 expression was higher only in NFPAs. The mRNA expression of MEK1, MEK2, ERK1, ERK2, c-MYC and CCND1 was similar in all groups. Our data indicate that in pituitary adenomas both the Raf/MEK/ERK and PI3K/Akt/mTOR pathways are upregulated in their initial cascade, implicating a pro-proliferative signal derangement upstream to their point of convergence. However, we speculate that other processes, such as senescence, attenuate the changes downstream in these benign tumours.